Risk of complications of pregnancy in women with type 1 diabetes: nationwide prospective study in the Netherlands. Issue 7445 (5th April 2004) - Evers, Inge M; de Valk, Harold W; Visser, Gerard H A
Abstract : Objective To investigate maternal, perinatal, and neonatal outcomes of pregnancies in women with type 1 diabetes in the Netherlands. Design Nationwide prospective cohort study. Setting All 118 hospitals in the Netherlands. Participants 323 women with type 1 diabetes who became pregnant between 1 April 1999 and 1 April 2000. Main outcome measures Maternal, perinatal, and neonatal outcomes of pregnancy. Results 84% (n = 271) of the pregnancies were planned. Glycaemic control early in pregnancy was good in most women (HbA1c  7.0% in 75% (n = 212) of the population), and folic acid supplementation was adequate in 70% (n = 226). 314 pregnancies that went beyond 24 weeks' gestation resulted in 324 infants. The rates of pre-eclampsia (40; 12.7%), preterm delivery (101; 32.2%), caesarean section (139; 44.3%), maternal mortality (2; 0.6%), congenital malformations (29; 8.8%), perinatal mortality (9; 2.8%), and macrosomia (146; 45.1%) were considerably higher than in the general population. Neonatal morbidity (one or more complications) was extremely high (260; 80.2%). The incidence of major congenital malformations was significantly lower in planned pregnancies than in unplanned pregnancies (4.2% (n = 11) v 12.2% (n = 6); relative risk 0.34, 95% confidence interval 0.13 to 0.88). Conclusion Despite a high frequency of planned pregnancies, resulting in overall good glycaemic control (early) in pregnancy and a high rate of adequate use of folic acid, maternal and perinatal complications were still increased in women with type 1 diabetes. Neonatal morbidity, especially hypoglycaemia, was also extremely high. Near optimal maternal glycaemic control (HbA1c  7.0%) apparently is not good enough.